IDENTIFIKASI BORAKS PADA PENTOL BAKSO YANG DI KELURAHAN AIR HITAM DENGAN PEREAKSI KULIT BUAH NAGA MERAH (Hylocereus polyhizus) - Lestari, Dwi; Dewi, Mutia; Ningsih, Suci Cahya; Hidayati, Hidayati (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
Borax is often misused to preserve various foods such as wet noodles, meatballs, rice cake, rhombus and so on. Red dragon fruit skin contains secondary metabolites, namely anthocyanin, anthocyanin is the most important and widespread dye in the skin of red dragon fruit, but the use of red dragon fruit peels has not been studied much naturally. The purpose of this study was to identify borax on the meatball sold in the Air Hitam district with the red dragon fruit skin reagent (Hylocereus polyhizus). This research is experimental with data collection techniques by accidental sampling. In this study used several samples of meatball pentol purchased at the meatball merchant located in Air Hitam Village by using dragon fruit peel and AgNO3 reagent as a comparison indicator. This research includes plant determination, sample collection, sample preparation, spike making, dragon fruit skin extract reagents and qualitative sample testing. Data analysis using descriptive analysis method. The results of the identification of borax on 5 meatball samples using color reagents from the extract (essence) of the red dragon fruit peel and AgNO3 reagent as a comparative indicator showed that all samples of the meatball obtained Negative results